The Decline of College Textbook Publishing: Cengage Learning and McGraw-Hill. - Carbaugh, Bob (American Economist, 2020)
America's college textbook publishers historically had a business model based on continuing profits and growth led by high prices. However, that model eroded as competition from the used-book market and rental textbooks resulted in falling textbook sales and losses for publishers. Textbook publishers are currently revising their business model so as to move away from printed textbooks to digital (online) educational materials. Also, publishers are downsizing their operations and undergoing mergers with each other to survive in the marketplace. The 2019 merger proposal of McGraw-Hill and Cengage Learning reflects the current problems of college textbook publishing: The merger would be between two financially weak companies that are attempting to reduce overhead and production costs and create additional revenue streams. However, the U.S. Department of Justice's concerns about the harmful effects on competition led to the companies' agreement to abandon their plans to merge in May 2020. JEL Classification : A00, K21, L22, L41